Diverticula of the gallbladder - Arias Segovia, Mesías (1964)
In conclusion, as you can see, the real Bibliar bladder diverticula are rare and undoubtedly congenital. The diagnosis is exclusively radiographic or pathological. For its rarity, clinically almost never mentioned. The symptoms, when it becomes clear as we have seen in this case is similar to a vesicular process either.